Covalent functionalization of decellularized tissues accelerates endothelialization - Eleonora Dal Sasso; Annj Zamuner; Andrea Filippi; Filippo Romanato; Tiziana Palmosi; Luca Vedovelli; Dario Gregori; José Luís Gómez Ribelles; Teresa Russo; Antonio Gloria; Laura Iop; Gino Gerosa; et al. (Bioactive Materials, 2021)
In the field of tissue regeneration, the lack of a stable endothelial lining may affect the hemocompatibility of both synthetic and biological replacements. These drawbacks might be prevented by specific biomaterial functionalization to induce selective endothelial cell (EC) adhesion. Decellularized bovine pericardia and porcine aortas were selectively functionalized with a REDV tetrapeptide at 10−5 M and 10−6 M working concentrations. The scaffold-bound peptide was quantified and REDV potential EC adhesion enhancement was evaluated in vitro by static seeding of human umbilical vein ECs. The viable cells and MTS production were statistically higher in functionalized tissues than in control. Scaffold histoarchitecture, geometrical features, and mechanical properties were unaffected by peptide anchoring. The selective immobilization of REDV was effective in accelerating ECs adhesion while promoting proliferation in functionalized decellularized tissues intended for blood-contacting applications.